Has the Euro Changed Business Cycle Synchronization? Evidence from the Core and the Periphery - Sybille Lehwald (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Using a Bayesian dynamic factor model, I examine the comovement of output, investmentand consumption growth among Euro area countries before and after the introduction of theEuro. For that purpose, I compare a pre-Euro period (19911998) to a Euro period(20002010) and identify a common Euro factor for each period separately. I find thatthe comovement of main macroeconomic variables and the common factor increases forcore Eurozone countries from the first to the second period, while it decreases for mostperipheral economies. This can be interpreted as a rise in business cycle synchronizationfor the core and a respective decline for the periphery.Different to the implications made by the endogeneity argument of currency areas(Frankel and Rose, 1998), my evidence suggest that the introduction of the Euro hasfostered imbalances between core and peripheral Eurozone countries.
Keywords: C11; C32; E32; F41; F42; 330; European business cycles; Euro; optimum currency area; core and periphery; dynamic factor analysis; Euro; Europäische Wirtschafts- und Währungsunion; Konjunktur; Entwicklungskonvergenz; Konjunkturzusammenhang; Zentrum-Peripherie-Beziehung; Europäische Wirtschafts- und Währungsunion